2021
DOI: 10.1017/dap.2021.38
|View full text |Cite|
|
Sign up to set email alerts
|

Using Twitter to track immigration sentiment during early stages of the COVID-19 pandemic

Abstract: Large-scale coordinated efforts have been dedicated to understanding the global health and economic implications of the COVID-19 pandemic. Yet, the rapid spread of discrimination and xenophobia against specific populations has largely been neglected. Understanding public attitudes toward migration is essential to counter discrimination against immigrants and promote social cohesion. Traditional data sources to monitor public opinion are often limited, notably due to slow collection and release activities. New … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 60 publications
(82 reference statements)
0
11
0
Order By: Relevance
“…We approximated these movements analysing changes in local populations. While this is not a serious constrain, it resonates with calls made elsewhere to triangulate digital trace data with other sources of information as we have done in this paper (Rowe et al 2021;Rowe et al 2022) .…”
Section: Discussionmentioning
confidence: 56%
“…We approximated these movements analysing changes in local populations. While this is not a serious constrain, it resonates with calls made elsewhere to triangulate digital trace data with other sources of information as we have done in this paper (Rowe et al 2021;Rowe et al 2022) .…”
Section: Discussionmentioning
confidence: 56%
“…They were also not perceived as "scapegoats" that were to be blamed given their status in society (39). This was in a way surprising given that other studies have shown that ostracism or other forms of discriminatory practises would be expected in a pandemic (40)(41)(42).…”
Section: Discussionmentioning
confidence: 91%
“…They also have designed an algorithm to find the top-involved users at various times using the user's involvement score. Similarly, Rowe et al [25] have analyzed the tweets using topic modeling and Valence Aware Dictionary and sEntiment Reasoner (VADER) with respect to immigrants. They have observed that there is a steady increase of negative attitudes towards the immigrants during the pandemic era.…”
Section: Related Workmentioning
confidence: 99%